2014
DOI: 10.1016/j.jadohealth.2014.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Assent in Research: The Voices of Adolescents

Abstract: Purpose Adolescents join clinical research after investigators obtain their positive agreement, or ‘assent.’ Although intended to respect adolescents, little is known about the views of adolescents or their parents regarding assent or research enrollment decisions. This study aimed to better understand perspectives of adolescent research participants and their parents about assent and parental permission. Methods Structured interviews were conducted with 13 through 17 year old teens, enrolled in clinical res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 18 publications
1
33
0
Order By: Relevance
“…Legally, the answer to the question of whether Adam has a right to know is "no." Due to his status as a minor, he is not legally authorized to consent (although many institutions require assent of minors, especially for research participation [33]), and hence he is not entitled to be informed of the benefits and burdens of the proposed therapy as his surrogates (i.e., his parents) are. And it would be unwise to cast his right-legal or moral-in terms of a multitude of elaborated human rights, only some of which inhere in persons who lack decisionmaking capacity (such as Adam) [34], as that would potentially distort or even trivialize the moral power that we have accorded rights by amplifying their breadth and scope.…”
Section: Resultsmentioning
confidence: 99%
“…Legally, the answer to the question of whether Adam has a right to know is "no." Due to his status as a minor, he is not legally authorized to consent (although many institutions require assent of minors, especially for research participation [33]), and hence he is not entitled to be informed of the benefits and burdens of the proposed therapy as his surrogates (i.e., his parents) are. And it would be unwise to cast his right-legal or moral-in terms of a multitude of elaborated human rights, only some of which inhere in persons who lack decisionmaking capacity (such as Adam) [34], as that would potentially distort or even trivialize the moral power that we have accorded rights by amplifying their breadth and scope.…”
Section: Resultsmentioning
confidence: 99%
“…It is also important to recognize that discordance is not necessarily negative, which is exactly the argument for requiring parental permission and adolescent assent. Parents and adolescents may weigh features of studies differently, 12, 13, 19, 20 and conversations between adolescents and parents can be used to foster developmental growth for the adolescent. 12 Particularly for studies involving sensitive topics or those studies focused on behaviors that the parents may be unaware of (such as sexual activity or substance use), it is critical to address the appropriate role of parents.…”
Section: Discussionmentioning
confidence: 99%
“…Other research has supported that adolescents and parents can be satisfied with a consent process that supports adolescent involvement and parental permission. 20 Thus, we must simultaneously advocate for adolescent participation and look for new models for parental involvement and consent.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the findings corresponded with other studies and showed that having the ability to say “No” decreases risky behaviors, such as smoking. [232425]…”
Section: Discussionmentioning
confidence: 99%